Therapeutic adherence and somatic symptom perception in patients with heart failure: a scoping review - Tri Andayani; Kumboyono Kumboyono; Lilik Supriati (Intelektual Pustaka Media Utama, 2026)
Heart failure is a chronic condition associated with high morbidity and frequent hospital readmissions, requiring effective self-management strategies. Therapeutic adherence and somatic symptom perception are essential components of self-management, enabling early symptom recognition and timely intervention. However, evidence regarding the relationship between these two factors remains limited. This scoping review aimed to map current evidence on the relationship between therapeutic adherence and somatic symptom perception in patients with heart failure and to identify influencing factors. The review followed the Joanna Briggs Institute methodology and PRISMA-ScR guidelines. Literature searches were conducted in ProQuest, ScienceDirect, Springer, and Google Scholar for studies published between 2016 and 2025. Eligible studies involved adult patients with heart failure and assessed therapeutic adherence and somatic symptom perception using validated instruments. Eight studies were included, comprising four cross-sectional studies, three randomized controlled trials, and one quasi-experimental study. Findings indicated a positive association between adherence to self-care behaviors and improved somatic symptom perception. Patients with consistent symptom monitoring demonstrated better recognition of early deterioration signs. However, a greater symptom burden was associated with lower adherence in several studies. Integrating symptom perception training, motivational strategies, and caregiver involvement may improve adherence, enhance early symptom detection, and reduce hospital readmissions.